Effect of GNPs on the Piezoresistive, Electrical and Mechanical Properties of PHA and PLA Films - Gonzalo Mármol; Usha Kiran Sanivada; Raul Fangueiro (Fibers, 2021)
Sustainability has become the primary focus for researchers lately. Biopolymers such as polyhydroxyalkanoate (PHA) and polylactic acid (PLA) are biocompatible and biodegradable. Introducing piezoresistive response in the films produced by PLA and PHA by adding nanoparticles can be interesting. Hence, a study was performed to evaluate the mechanical, electrical and piezoresistive response of films made from PHA and PLA. The films were produced by solvent casting, and they were reinforced with graphene nanoplatelets (GNPs) at different nanoparticle concentrations (from 0.15 to 15 wt.%). Moreover, cellulose nanocrystals (CNC) as reinforcing elements and polyethylene glycol (PEG) as plasticizers were added. After the assessment of the nanoparticle distribution, the films were subjected to tests such as tensile, electrical conductivity and piezoresistive response. The dispersion was found to be good in PLA films and there exist some agglomerations in PHA films. The results suggested that the incorporation of GNPs enhanced the mechanical properties until 0.75 wt.% and they reduced thereon. The addition of 1% CNCs and 20% PEG in 15 wt.% GNPs’ tensile values deteriorated further. The PHA films showed better electrical conductivity compared to the PLA films for the same GNPs wt.%. Gauge factor (GF) values of 6.30 and 4.31 were obtained for PHA and PLA, respectively.